Beginning programming with C++ for dummies - Davis, Stephen R., 1956-; Safari eBooks (Hoboken, N.J. : Wiley, 2010)
"Learn to think like a programmer and understand how C++ works, create programs and get bugs out of your code, [and] master basic development concepts and techniques in C++"--Cover.
Description based on print version record.
Includes index.
Keywords: C++ (Computer program language); Electronic books